Laser applications in arts and culture: An example on the construction of tiered umbrellas - Wuttichai Phae-ngam; V. Tapanwong; K. Jeraratcharatthorn; P. Sriwaralak; Theeranon Chaiyakun; Surachart Kamoldilok; V. Kosalathip; Kittisakchai Naemchanthara; Pichet Limsuwan (Journal of Laser Applications, 2024)
Tiered umbrella or in Thai called Chat means a high decoration or decoration of honor, a type of umbrella that is stacked up in layers along a single axis. At present, in Thailand, the tiered umbrellas are seen in three important places including (1) on the top of the pagoda of various temples, (2) inside the ordination hall of temples, and (3) inside the Grand Palace for the king and the royal family. In the past, a tiered umbrella was made from brass because its color was similar to gold. Constructing each set of tiered umbrellas requires a skilled technician and takes a lot of time. At present, laser cutting of metals has been widely used in the production section of the industry. This is due to the advantages of laser cutting that include narrow kerf width, smooth cutting edges, high cutting speed, reduced material waste, no tool wear, and easy automation and manipulation even for complex shapes. In this work, an example for the construction of seven-tiered umbrellas from stainless steel sheets using a high-power CO2 laser was reported. The results show that the total working time for the construction of a seven-tiered umbrella is about 113 h, which is much less time compared to 3–6 months taken by craftsmen. Therefore, this method can preserve the construction of tiered umbrellas in Thailand even though craftsmen are scarce at present.
Keywords: Laser Material Processing Techniques